Real Time Monitoring of the State of Smart Grid - Gudžius, S.; Gvozdas, V.; Markevičius, L. A.; Morkvėnas, A. (Elektronika ir Elektrotechnika, 2010)
The paper describes the mathematical models of fast electromagnetic processes analysis and its application principles for normal, fault, post-fault regimes identification of electricity distribution networks and fault place location. Algorithms based on fast electromagnetic processes identification models have been created and implemented in distribution network state identification terminals. Terminals have been mounted in six substations of Lithuanian electricity distribution utility and deliver real-time network state identification information to the dispatcher centre. The analysis of the results and algorithms application for the distribution network regimes identification is presented, and the further development perspectives based on fast electromagnetic transient analysis models are discussed.